AI in English Classrooms: Voicing Junior High School Teachers’ Experience - Zurriat Nyndia Rahmawati; Muhammad Rizal Akbar Zamzami; Bila Nastiti Tasaufi (STKIP Taman Siswa Bima, 2025)
AI tools serve various purposes in education, from creating learning materials to improving teaching quality. AI also serves a beneficial role in enhancing teacher competences. Integrating AI in education is also seen as vital for equipping students for the future challenges. This paper aims to voice the experience of English teachers in Junior High School from three regions in East Java. The data in this qualitative research were collected through questionnaires and interview. The data showed that the majority of teachers have been using AI for text, image, and video generation system. AI is also used for instruction and administrative functions. However, it brings some drawbacks such as dependency and lower critical thinking. The teachers must be mindful of AI's potential downsides for themselves and the students; emphasizing the need for careful implementation. Therefore, providing teachers with necessary skills through ongoing professional development is essential to ensure AI effectively enhances learning quality.